The European Court of Human Rights at the grassroots level: who knows what about religion at the ECtHR and to what effects? - Fokas, Effie (Religion, state & society, 2017)
In the last 25 years, the European Court of Human Rights (ECtHR) has been increasingly addressing some of the most divisive religion-related issues facing European societies. In the process, it has been setting from above certain parameters for religious pluralism in Europe. The present contribution draws on research designed to bring the Court's influence on religious pluralism into sharp focus, but from the ground up. We know more or less the direct effect of the Court in terms of implementation of its decisions. But we lack understanding of its indirect effects in terms of whether and how its case law mobilises grassroots actors (rights consciousness raising, agenda setting, bargaining in the shadow' of the Court). Such understanding presupposes insight into levels of awareness of the ECtHR and its religion-related case law: who knows what about religion at the ECtHR and to what effects? This contribution presents results of a study engaging social actors in four countries.